The Intracellular Distribution of Folate Derivatives in Pea Leaves - Chan Sherwin Y.; Cossins Edwin A. (Pteridines, 2003)
After hydrolysis of polyglutamate derivatives, leaf extracts of pea (Pisum sativum L.) seedlings were examined for individual folates using high Performance liquid chromatography and microbiological assays employing Lactobacillus rhamnosus and Pediococcus acidilactici. 14-day seedlings contained 0.17±0.01 nmol folate mg-1 protein that was predominantly methylated and associated with the cytosolic fraction. Percoll gradient-purified mitochondria and chloroplasts contained 11.0±2.3% and 8.4±0.6% of cellular folate, respectively. Mitochondrial folates (0.47±0.11 nmol folate mg-1 protein) were predominately (90%) formylated and unsubstituted. In contrast, chloroplasts contained a less concentrated (0.02±0.001 nmol folate mg-1 protein) folate pool consisting of approximately 30% methylated folate. The total folate content of pea leaves increased by 40% when dark-grown (etiolated) 9-day seedlings were exposed to light for 48 hours. During this light treatment, the mitochondrial folate pool, on a per mg protein basis, increased 10-fold. This light treatment also changed the composition of the mitochondrial folate pool with a shift occurring from methylated to formylated and unsubstituted derivatives. These changes in the folates of greening tissues are discussed in relation to the metabolism of glycine and serine that accompanies photorespiration in leaf tissues.